HP-1 inhibits the progression of ccRCC and enhances sunitinib therapeutic effects by suppressing EMT. (1st November 2019) - Fang, Liang; Zhang, Yongzhen; Zang, Yuanwei; Chai, Rong; Zhong, Guangxin; Li, Zeyan; Duan, Zhichen; Ren, Juchao; Xu, Zhonghua
Highlights: HP-1 treatment inhibited the proliferation of renal cancer-derived cell lines. HP-1 can inhibit the expression of CIP2A. The combined HP-1/sunitinib treatment resulted in increased anticancer effects. Abstract: Trametes robiniophila Murr (Huaier) has been used for many years as an adjuvant treatment for tumors. Sunitinib is the first-line therapy for end-stage renal cancer, but its side effects and drug resistance limit its clinical application. Cell counting kit- 8 (CCK-8), colony formation, scratch, and Transwell assays showed that Huaier polysaccharide (HP-1) reduced tumor progression. Its combination with sunitinib elicited stronger antitumor effects, including induction of apoptosis and cycle arrest. HP-1-induced effects depended on CIP2A downregulation and suppression of the EMT process. Moreover, qPCR and western blotting experiments showed that CIP2A downregulation was particularly pronounced after treatment with the combination therapy and was associated with EMT suppression. In addition, the HP-1/sunitinib combination inhibited the PI3K/Akt/VEGFR pathway, reducing the expression of pathway-related proteins. The HP-1-induced enhancement of sunitinib effects on tumor growth were also observed in vivo in a xenograft mouse model. Overall, these results indicated that HP-1 exerted antitumor effects against clear cell renal cell carcinoma (ccRCC) and enhanced the therapeutic efficacy of sunitinib.